Model design to develop online web based questionnaire - Julian Wesley; Fifilia Fifilia; Cynthia Catrine; Dennis Antony; Ferdian Rizky Estefan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
This research aims to create a web-based application for sharing questionnaires. The developed features are creating questionnaires, sharing questionnaire in the dashboard, filter the questionnaire as the requested criterias, exchange the rewarded coins for gifts, export questionnaire data to a document, set a limit for the questionnaire for each device. The development will be using data collecting using questionnaire and literature study. Then, software development life cycle (SDLC) waterfall research methodology will be used for the website system development. Result of this research will be a website application that will be used for questionnaire maker so that they can reach the respondent count target, have a suitable respondent (minimize respondent who does not meet the criteria), and also can collect more validated data.